2022
DOI: 10.21470/1678-9741-2021-0462
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Actions of Thymoquinone, Silymarin, and Curcumin on Experimental Aortic Ischemia-Reperfusion Model in Wistar Albino Rats

Abstract: Introduction Medical improvements are needed to prevent ischemia-reperfusion injury in thoracoabdominal aortic surgery. The aim of this study was to determine the antioxidant effects of thymoquinone, silymarin, and curcumin against ischemia-reperfusion injury associated with abdominal aorta. Methods Twenty-five Wistar albino rats were included in the study. Sham, control, and treatment (thymoquinone, silymarin, and curcumin) groups were set in equal numbers. Ischemia-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When the studies in the literature are examined, curcumin has shown many positive effects on TAS and TOS with its antioxidant properties [17,18] Consistent with the literature, TAS was found to be significantly lower in the curcumin group in our study (p=0.021). Although TOS was low in the curcumin group, it was not significantly different from other groups (p=0.069).…”
Section: Discussionsupporting
confidence: 89%
“…When the studies in the literature are examined, curcumin has shown many positive effects on TAS and TOS with its antioxidant properties [17,18] Consistent with the literature, TAS was found to be significantly lower in the curcumin group in our study (p=0.021). Although TOS was low in the curcumin group, it was not significantly different from other groups (p=0.069).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, TAS and TOS measurements did not improve in the silymarin-treated groups (S + CLP, CLP + S). This may indicate that the biochemical improvement reported in the literature (98,99) does not significantly contribute to tissue damage observed in sepsis.…”
Section: Discussionmentioning
confidence: 84%
“…In previous studies, silymarin and dexmedetomidine have been studied together with different combinations (98,(111)(112)(113)(114)(115)(116), but no study has been performed in which these two agents were used together. Thus, the present study aimed to investigate the effects of these two agents used together.…”
Section: Discussionmentioning
confidence: 99%